Development Of Semi-Solid Self-Emulsifying Drug Delivery System (Sedds) Using Liquid Model Drug For Oral Drug Delivery Application - Abu Bakar, Syazana (2022)
A study was conducted to formulate a semi-solid SEDDS with enhanced bioavailability using Gelucire® 44/14 as the self-emulsifying agent and a tocotrienols mixture (EVNol™ 50%) as the liquid model drug. A series of formulations with different proportions of tocotrienol extract and Gelucire® 44/14 were prepared and evaluated. Finally, a formulation with 1:1 ratio of tocotrienols to Gelucire® 44/14 with the addition of 2.5% of propylene glycol was found most suitable to obtain a semi-solid SEDDS with satisfactory self-emulsifying properties. From a series of in vitro studies, the formulation was able to self-emulsify under gentle agitation and formed an oil in water emulsion within 3 minutes upon contact with the dissolution media. The emulsion formed was stable, with the emulsion particle size distribution achieving nano-range. Subsequently,